Does education affect attitudes towards immigration? Evidence from Germany - Shushanik Margaryan; Annemarie Paul; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Using data from the German Socio-Economic Panel and exploiting the staggered implementation of a compulsory schooling reform in West Germany, this article finds that an additional year of schooling lowers the probability of being very concerned about immigration to Germany by around six percentage points (20 percent). Furthermore, our findings imply significant spillovers from maternal education to immigration attitudes of her offspring. While we find no evidence for returns to education within a range of labour market outcomes, higher social trust appears to be an important mechanism behind our findings.
Keywords: I26; J15; J62; 330; attitudes towards immigration; intergenerational effects; schooling; externalities; instrumental variables estimation